On the food of northern krill Meganyctiphanes norvegica in relation to its vertical distribution - Lass, S; Tarling, G; Patti Virtue; Matthews, J; Mayzaud, P; Buchholz, F (2001)
The feeding behaviour of northern krill (Meganyctiphanes norvegica) was studied in populations from the Clyde Sea and the Kattegat during summer and winter. The food spectrum in the stomachs was analysed using traditional taxonomic methods and biochemical techniques. The vertical migration behaviour of krill was monitored through a 30 h series of net samples, whilst the trophic environment was characterised through accompanying quantitative analyses on the depth distribution and biomass of copepods and phytoplankton. Krill was found to be more carnivorous in the Kattegat than in the Clyde Sea, which correlated with the higher ratio of copepod to phytoplankton biomass found in the Kattegat compared with the Clyde Sea. High levels of fatty alcohols and other lipid markers in the stomach contents of Kattegat krill were also indicative of a carnivorous diet. Other food sources included detritus, terrestrial material and other euphausiids, underlining the opportunistic nature of northern krill in its choice of prey items. Analyses of stomach and intestinal fullness over a diel cycle showed significant variations with time in the Clyde Sea but not in the Kattegat. However, a diel cycle in the rate of ingestion was evident at both locations when comparing the copepod mandibles in the stomachs to the distribution of copepods in the environment. The fact that deep-living Calanus was not a major prey item suggested that there was little feeding activity during the daytime, when the krill occupied the deeper layers. Instead, the majority of mandibles were from species that were dominant in the upper layers, e.g. the genera Temora and Pseudocalanus. The fact that krill caught in the daytime contained the same relative composition of mandibles in the stomach as those caught at night is probably explained by a cessation in daytime feeding activity and retention of the mandibles from the night before. It is proposed that krill in the Clyde Sea area and the Kattegat show a diel rhythm in feeding activity that is believed to be ...